Rancang Bangun Aplikasi Analisis Laporan Realisasi Anggaran Pembangunan Gedung mengacu Pada Standar Nasional Indonesia (Studi Kasus: CV. Citra Mandiri Solution) - Hidayat, Mohammad Rizal; Widodo, Arifin Puji; Tyas, Ayu Ning (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
CV. Mandiri Citra Solution is a company engaged in construction that stood since 2005. During the year 2012 the company was already working on 85 projects and the project value ranging from 5 million to 500 million. Several of projects in the year 2012, there are some projects that do not generate gross profit. From the analysis of the existing system the company uses today, is by comparing the LRA with RAB, there is some difference in the cost is known. However, such systems cannot provide decision support in the form of information about the cause of the difference in cost. In addition the system has no reference in analyzing the LRA, the LRA so that the results of the analysis cannot be used as a decision support for making RAB on the next project. From the description above, the issue will be the development of analytical applications LRA, which refers to the Indonesian National Standard (SNI). Analyze the processes that occur in the LRA in this application is by comparing the LRA, RAB and design costs refer to the SNI. In addition to preparing and analyzing the LRA, the app also comes with making financial reports to the making cashflow in order to be easier to see the profit or loss from the company. From the test results LRA analysis applications with reference to ISO concluded that the system can run the business process analysis of the LRA, issuing reports and information required by the company. Keyword: budget realisation, construction information system